Express (9x^2 + 43x + 8)/(3+x)(1-x)(2x+1) in partial fractions.

A/(3+x) + B/(1-x) + C/(2x+1) = (9x^2 + 43x + 8)/(3+x)(1-x)(2x+1)So... A(1-x)(2x+1) + B(3+x)(2x+1) + C(3+x)(1-x) = (9x^2 + 43x + 8)Insert x=1Equation becomes 12B = 60 so B = 5.Then insert x=-3Equation becomes -20A = -40 so A = 2Then insert x = -0.5Equation becomes 3.75C = -11.25 so C = -3.
So answer is 2/(3+x) + 5/(1-x) - 3(2x+1).

Answered by Abhik V. Maths tutor

5916 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the equation of the tangent to the circle x^2 + y^2 + 10x + 2y + 13 = 0 at the point (-3, 2)


A circle has equation: (x - 2)^2 + (y - 2)^2 = 16. It intersects the y-axis (y > 0) at point P and the x-axis (x < 0) at point Q. Find the equation of the line connecting P and Q and of the line perpendicular to PQ passing through the circle's centre.


Differentiate with respect to x: y=2^x


Given a function f(x)=3x^2+5x-1, find its derivative.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences